Plasma harmonics - Ganeev, Rashid A. (Pan Stanford Publishing, 2014)
Plasma harmonics is a new field of laser spectroscopy. The use of the solid elements of the periodic table, together with thousands of complex solid-state samples, largely extends the range of materials employed in plasma harmonics in contrast to the few light rare gases that are typically used. Thus the exploration of practically any available solid-state material through nonlinear spectroscopy comprising laser ablation and harmonic generation can be considered a new tool for materials science. Plasma harmonic spectroscopy exploits the spectral and structural properties of various ablated solid-state materials by propagating short laser pulses through laser-produced plasma and generating high-order harmonics of ultrashort laser pulses. The book describes the special features of plasma harmonics in laser-produced ablation plumes and discusses a wide range of nonlinear medium characteristics that can be produced by varying the conditions of laser plume production on the surface of a solid. This book compiles and details cutting-edge research in science and medicine from the interdisciplinary team of the Michigan Nanotechnology Institute for Medicine and Biological Sciences, who are currently revolutionizing drug delivery techniques through the development of engineered nanodevices. Edited by Istvan J Majoros and James Baker, Jr., two prominent nanotechnology researchers, this book is designed for workers involved in nanotechnology, macromolecular science, cancer therapy, or drug delivery research.